Private Bill : In Love and War. - Cassidy, Barrie (Melbourne University Press, 2014)
Barrie Cassidy's dad Bill survived more than four years as a prisoner of war in World War II. He first saw conflict on Crete in May 1941, during the only large-scale parachute invasion in wartime history. Just four days later, Bill was wounded and eventually captured. Twice he tried to escape his internment with horrific consequences. He suffered greatly but found courageous support from his fellow prisoners. His new wife Myra and his large family thought he was dead until news of his capture finally reached them. Back home, Myra too was a prisoner of sorts, with her own secrets. Then, 50 year.